Les questions de santé dans les magazines pour adolescents - François Bissege (Communication)
Based on a content analysis of the editorial content of four teen magazines published in France and on interviews with their editors, this article examines how these magazines deal with health issues. The author shows that what is meant by health issues refers broadly to a wide range of concerns specific to teenagers. He also claims that the magazines’ mode of argument regarding health issues consists in appropriating the voiced opinions of their readers.